2017
DOI: 10.1117/12.2258617
|View full text |Cite
|
Sign up to set email alerts
|

Electrical breakdown detection system for dielectric elastomer actuators

Abstract: Electrical breakdown of dielectric elastomer actuators (DEAs) is an issue that has to be carefully addressed when designing systems based on this novel technology. Indeed, in some systems electrical breakdown might have serious consequences, not only in terms of interruption of the desired function but also in terms of safety of the overall system (e.g. overheating and even burning). The risk for electrical breakdown often cannot be completely avoided by simply reducing the driving voltages, either because com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…To facilitate observation of the breakdown site and healing no electrode was used and similar pin-hole breakdown defects were formed when metallic electrodes were used ( Figure S1). The pristine elastomer experienced electrical breakdown at a 9.5 kV voltage (and electric field of 32.8 kV mm -1 ), as shown in Figure 1(A)-(1) which leads to the formation of a carbonized [18] pin-hole of ~ 90 µm in diameter, as shown in Figure 1(B). Both the upper and lower surfaces of the elastomer had carbon deposits produced near the defect, due to the reaction of the vaporized material with air during breakdown.…”
Section: Observation Of Self-healed Mgsbs Elastomer After Electrical mentioning
confidence: 99%
“…To facilitate observation of the breakdown site and healing no electrode was used and similar pin-hole breakdown defects were formed when metallic electrodes were used ( Figure S1). The pristine elastomer experienced electrical breakdown at a 9.5 kV voltage (and electric field of 32.8 kV mm -1 ), as shown in Figure 1(A)-(1) which leads to the formation of a carbonized [18] pin-hole of ~ 90 µm in diameter, as shown in Figure 1(B). Both the upper and lower surfaces of the elastomer had carbon deposits produced near the defect, due to the reaction of the vaporized material with air during breakdown.…”
Section: Observation Of Self-healed Mgsbs Elastomer After Electrical mentioning
confidence: 99%
“…Current electro-adhesives based on electronic conductors and insulating dielectric layers, however, are typically limited by the need for applied potentials in the range of several kV, which, in addition to presenting safety concerns and requiring specialized circuit elements compatible with high voltages, [21] can easily lead to dielectric breakdown and corresponding irreversible device failures. [22,23] One strategy to reduce operating voltage is to decrease the dielectric layer thickness of the electro-adhesives, as a standard parallel plate capacitor model would suggest that electrostatic force is inversely proportional to the square of the dielectric thickness. [5,24] Indeed, Chen et al [4] demonstrated that the use of a thin (< 0.8 µm) parylene dielectric layer prepared by chemical vapor deposition provided an electro-adhesive surface that could support a shear stress of 120 kPa with an operating voltage of only 50 V. Similarly, Rivaz et al [13] used a thin (~ 12.5 µm) polyimide dielectric layer that supported a 6 kPa shear stress at 250 V. However, reliable fabrication of mechanicallyrobust and defect-free dielectric layers becomes challenging as the thickness of the dielectric layer is further decreased, [4] and operation in the range of only a few volts has not previously been possible with dielectric electro-adhesives.…”
mentioning
confidence: 99%
“…There were many reasons that caused the failure of dielectric elastomers as shown in the literature, [55,56] which limited the extensive application of DEAs. Some ways have been used to detect the different breakdowns of DEAs, [57][58][59] which may be further applied to detect the failure of the DE layers in multilayer. Once the damaged layers may be replaced, the elec-trode layer in the multilayer structure fabricated by the vacuum lamination process may be recycled to form the new device.…”
Section: Artificial Muscle Demonstrationsmentioning
confidence: 99%